KEWENANGAN PENGADILAN AGAMA KUDUS DALAM PENYELESAIAN SENGKETA WAKAF - Wara Hastuti, Qurratul Aini (ZISWAF, 2014)
Kudus Religious Courts jurisdiction to resolve disputes of waqf. Becausethe waqf property transaction provisions should be made in the form oftransactions in accordance with Islamic law (Shariah transactions), althoughthere are non-Muslim behalf and legal entities that are not based on IslamicLaw, it is considered as a submission to the Law of Islam.